Association mapping and genetic dissection of drought-induced canopy temperature differences in rice. (17th December 2019) - Melandri, Giovanni; Prashar, Ankush; McCouch, Susan R; van der Linden, Gerard; Jones, Hamlyn G; Kadam, Niteen; Jagadish, Krishna; Bouwmeester, Harro; Ruyter-Spira, Carolien
Abstract : Canopy temperature, detected by thermal imaging, is a good predictor of rice yield performance under drought and shows genetic variation in an association mapping panel. Abstract: Drought-stressed plants display reduced stomatal conductance, which results in increased leaf temperature by limiting transpiration. In this study, thermal imaging was used to quantify the differences in canopy temperature under drought in a rice diversity panel consisting of 293 indica accessions. The population was grown under paddy field conditions and drought stress was imposed for 2 weeks at flowering. The canopy temperature of the accessions during stress negatively correlated with grain yield ( r = –0.48) and positively with plant height ( r =0.56). Temperature values were used to perform a genome-wide association (GWA) analysis using a 45K single nucleotide polynmorphism (SNP) map. A quantitative trait locus (QTL) for canopy temperature under drought was detected on chromosome 3 and fine-mapped using a high-density imputed SNP map. The candidate genes underlying the QTL point towards differences in the regulation of guard cell solute intake for stomatal opening as the possible source of temperature variation. Genetic variation for the significant markers of the QTL was present only within the tall, low-yielding landraces adapted to drought-prone environments. The absence of variation in the shorter genotypes, which showed lower leaf temperature and higher grain yield, suggests that breeding for high grain yield in rice under paddy conditions has reduced genetic variation for stomatal response under drought.